Electrostatic Interaction between Soy Proteins and Pectin in O/W Emulsions Stabilization by Ultrasound Application - Albano, Kivia M. [UNESP]; Cavallieri, Ângelo Luiz Fazani; Nicoletti, Vânia R. [UNESP] (Springer Nature, 2020)
Proteins and polysaccharides can play the part of emulsifiers and stabilizers, yet emulsions stabilization may be improved through a protein:polysaccharide complexation based on electrostatic interactions. The chosen homogenization method and the protein:polysaccharide ratio at an adequate pH may affect complexation and its ability as an emulsion stabilizer. We evaluate the effects of ultrasound homogenization and soy protein isolate (SPI) and high methoxyl pectin (PEC) ratio to generate protein:polysaccharide complexes by electrostatic interactions. Moreover, emulsions stabilized by SPI:PEC complexes with 5, 10, 15 % soybean oil contents were evaluated after sonication to assess emulsions stability improvements. SPI and PEC showed strong interaction at pH 3.5, with higher complexation at higher protein ratio (4:1). Sonication reduced complex particle size, creating homogeneous and shear-thinning systems. SPI:PEC 1:1 emulsions had Newtonian behavior, smaller droplets, and remained stable for seven days. At SPI:PEC ratio of 4:1 emulsions had shear-thinning behavior, yet larger droplets and high creaming indexes, thus indicating destabilization by gravitational separation with cream phase and showing droplets with bimodal distribution (1.3-200 μm). Through heating-cooling ramps, temperature effect on rheological behavior of emulsions and pure biopolymers was assessed. 4:1 emulsions showed rheological behavior with a predominant effect of SPI, whereas 1:1 emulsions predominantly showed pectin characteristics. Emulsion stability was greatly affected by SPI:PEC ratio, since the pectin proportion had a strong influence on the emulsions behavior. Moreover, sonication was a fundamental parameter to increase SPI:PEC complexes effectiveness as emulsion stabilizers and use these systems to formulate foods with low oil contents.
Keywords: Complex Coacervation; Droplet size distribution; Emulsion stability; High Methoxyl pectin; Rheology; Sonication